Contribution of the Umayyad Dynasty to the Development of Islamic Civilization (661-750 AD) - Zein, Nashrurrahman (El Tarikh : Journal of History, Culture and Islamic Civilization, 2022)
The Umayyah dynasty was a classical Islamic era government which was often seen as weak when compared to the Khulafaurrasyidin and Abbasid dynasty.  This is partly due to the negative image that has developed among historians, especially as a result of the political developments that occurred at that time.  Three things were seen as "sins" of the Umayyad dynasty, namely changing the state system (Daulah Islam) from the previous "democracy" (Syuro) to a monarchy system, the caliphs focused more on the conquest process so that they neglected the fostering of civilization, and the dominance of the Arabs in government  .  Therefore, this paper reviews the role and contribution of the Umayyad dynasty in the process of Islamic development.  This paper uses a historical method consisting of heuristics, verification, interpretation, and historiography, and uses a political approach to focus its analysis.  From the results of the studies that have been carried out, several important points were found related to the strategic role of the Umayyad dynasty in history, namely (1) political stabilization, (2) regional expansion, (3) infrastructure development, and (4) Islamic preaching.  These four things are among the reasons for the advancement of the golden age (Golden Age) in the era of the Abbas dynasty. Keywords: Development, Civilization, Umayyad Dynasty.